2012
DOI: 10.1080/01652176.2012.677866
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of a gonadotropin-releasing hormone (GnRH) analog for the treatment of tertiary hypogonadism (GnRH deficiency) in a 5-year-old Belgian Blue bull

Abstract: A bull was referred for a progressive oligoasthenotheratozoospermia that resulted in a unsuitable seminal quality for the cryopreservation. Breeding soundness evaluation results suggested gonadal dysfunction. Because of the lack of normal ranges for these hormones in the bull, in this study, the hypogonadism and the site of the dysfunction (hypothalamus) were diagnosed by the gonadotropin-releasing hormone (GnRH) stimulation test. The evaluation of pituitary and testicular responsiveness by a GnRH stimulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In our study, bulls treated with GnRH showed better semen characteristics than other groups. This is in agreement with Contri et al (2012), who reported that the continuous administration of a low dose of a GnRH analog resulted in recovery of the function of the testis, in corroboration with the improvement of semen characteristics to normal within 9 weeks. As a consequence, the time necessary to improve semen quality in the treated bull being 8-9 weeks corresponds to the time spermatogenesis takes as reported in the literature (Barth and Oko, 1989).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, bulls treated with GnRH showed better semen characteristics than other groups. This is in agreement with Contri et al (2012), who reported that the continuous administration of a low dose of a GnRH analog resulted in recovery of the function of the testis, in corroboration with the improvement of semen characteristics to normal within 9 weeks. As a consequence, the time necessary to improve semen quality in the treated bull being 8-9 weeks corresponds to the time spermatogenesis takes as reported in the literature (Barth and Oko, 1989).…”
Section: Discussionsupporting
confidence: 92%
“…From the age of 18 months, the bull was successfully used for semen production in an artificial insemination center. However, at late age, the bull showed a progressive decrease in semen characteristics that involved sperm concentration and volume, motility and sperm abnormalities that resulted in an unsuitable quality of semen for cryopreservation (Contri et al, 2012). If the animals reach puberty and sexual maturity at early age, more benefit would be obtained from their productive life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classically, the evaluation of the testicular function of the bull always includes semen analysis [ 49 ]. All diseases localized in the testis (orchitis, hypoplasia, degeneration, hypogonadism, torsion, neoplasia) may cause a reduction in the quality of semen [ 50 , 51 ]. However, the evaluation of the seminal material provide information on the spermatogenesis started about 61 d before [ 2 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study used 18 Ongole Crossbred bulls at the age of 3-5 years with a motility condition of ≤40% (Contri et al, 2012). Semen was collected using an artificial vagina.…”
Section: Research Materialsmentioning
confidence: 99%